PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SDN 040 PASAWAHAN PADA MATERI SUMBER DAYA ALAM - Wiwi Noorfaedah (GoAcademica Research dan Publishing, 2022)
Static and monotonous learning is one of the obstacles and obstacles that arise in every learning process. The mistake in choosing a learning model that is suitable for the characteristics of students in a learning place is also an obstacle in the learning process. This study aims to determine and improve the learning outcomes of class IV students at SDN 040 Pasawahan on natural resources material. The type of research used is Classroom Action Research (CAR). The subjects of this study were 30 grade IV students at Public Alementary Cchool 040 Pasawahan. This study began with a pre test with the aim of knowing students' initial abilities before carrying out class action. The results of the pre-test evaluation showed that only 10 (33.33%) students had completed or fulfilled the school's Minimum Completeness Criteria with an average score of 65. Meanwhile, 20 (66.67%) students had not yet completed with an average score of 48, and class average value of 55.45. Furthermore, the researchers took action in cycle I. The results of the evaluation in cycle I were 22 (73.33%) students who succeeded in achieving the Minimum Completeness Criteria score with an average class score of 70, and 8 students (26.67%) had not achieved the Minimum Completeness Criteria score. with an average grade of 56, and an average grade of 70. Thus, class IV students at Public Alementary Cchool 040 Pasawahan have achieved mastery learning with an average grade of 70. In cycle II there were 28 (93.33%) students who succeeded reached the Minimum Completeness Criteria score with an average class score of 80, and 2 students (6.67%) had not reached the Minimum Completeness Criteria score. Thus the researcher did no longer take action in cycle III.